2002
DOI: 10.1161/hc1102.105264
|View full text |Cite|
|
Sign up to set email alerts
|

BG9719 (CVT-124), an A 1 Adenosine Receptor Antagonist, Protects Against the Decline in Renal Function Observed With Diuretic Therapy

Abstract: Background-Adenosine may adversely affect renal function via its effects on renal arterioles and tubuloglomerular feedback, but effects of adenosine blockade in humans receiving furosemide and ACE inhibitors is unknown. Methods and Results-This was a randomized, double-blind, ascending-dose, crossover study evaluating 3 doses of BG9719 in 63 patients with congestive heart failure. Patients received placebo or 1 of 3 doses of BG9719 on 1 day and the same medication plus furosemide on a separate day. Renal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
208
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(224 citation statements)
references
References 18 publications
10
208
0
6
Order By: Relevance
“…An A 1 AR antagonist, BG9719 (CVT-124), was in Phase II clinical trials (now discontinued) for the treatment of acute renal disorders in patients with congestive heart failure 159,160 . However, BG9719 contains an epoxide group, which is potentially chemically reactive.…”
Section: Ars As Targets In Renal System Disordersmentioning
confidence: 99%
“…An A 1 AR antagonist, BG9719 (CVT-124), was in Phase II clinical trials (now discontinued) for the treatment of acute renal disorders in patients with congestive heart failure 159,160 . However, BG9719 contains an epoxide group, which is potentially chemically reactive.…”
Section: Ars As Targets In Renal System Disordersmentioning
confidence: 99%
“…Adenosine A1 receptor antagonists may increase diuresis and improve renal function in patients with ACHF [70].…”
Section: New Agentsmentioning
confidence: 99%
“…6 Several studies, which were mainly designed for HFrEF patients, reported that loop diuretic use was associated with increased morbidity and mortality. [7][8][9][10][11] It is also true, however, that there is no alternative medication to loop diuretics to effectively relieve congestive symptoms and that it is difficult to perform a randomized clinical trial from an ethical point of view.…”
mentioning
confidence: 99%